PENGARUH MEDIA LEAFLET TERHADAP PENGETAHUAN SIKAP TENTANG KELELAHAN KERJA PADA TENAGA KERJA BONGKAR MUAT - Muhammad Evendi Halulanga; Andi Nadya Eka Putri; Nadia Muthia Hanifah Amrin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Fatigue at work is thought to be one of the causes of workplace accidents, so more focused attention is needed on the workforce to overcome this by encouraging adequate sleep, exercise, and a balanced diet. This research used a quantitative approach, employing a pre-experimental design with a one-group pre-test and post-test design. The study involved 22 participants who were loading and unloading workers. Research data was obtained through direct observation using questionnaires, then processed using SPSS and presented in the form of tables along with explanations.The results of the study show that educationusing leaflets as a method for OSH education obtained significant results in increasing knowledge (p=0.002) and attitudes (p=0.003) in controlling work fatigue in loading and unloading work.Keywords: Leaflets; knowledge; attitude; work fatigue.